Mediterranean Diet Is Associated with Lower Breast Cancer Risk in the Framingham Offspring Cohort Study. (29th May 2020) - Yiannakou, Ioanna; Singer, Martha; Moore, Lynn l; Jacques, Paul
Abstract: Objectives: We examined the prospective association between a Mediterranean diet pattern using four separate a priori indices of adherence and breast cancer risk in the Framingham Offspring (FOS) cohort. Methods: The four indices included in this study reflect two different approaches to measuring adherence to a Mediterranean diet: a. scores based on population food intake distributions (i.e., the alternate Mediterranean Diet (aMED) and Mediterranean Diet (MDS) score); and b. scores based on recommended intakes of relevant foods (i.e., Mediterranean Style Dietary Pattern (MSDP) and Mediterranean Diet (MeDiet) scores). The scores were derived from a semi-quantitative food frequency questionnaire. Subjects included 1703 women, aged 30 years old and older, who were free of prevalent cancer. Each score was classified into three categories (low, moderate, and high) to evaluate the association between the Mediterranean diet and breast cancer risk (overall, post-menopausal, and hormone receptor positive) from 1991 through 2014. Cox proportional-hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusting for confounding by age, physical activity, waist-to-height ratio, pack-years of cigarette smoking, supplement use, diabetes status, age at menopause and total calorie intake. Results: During a median follow-up of approximately 18 years, 93 breast cancer cases were documented. Women in the highest category of MSDP score or MeDiet score had approximately 45% lower breast cancer risks than women in the lowest categories (MSDP high category HR:0.56, 95% CI: 0.33–0.94; MeDiet high category HR: 0.55, 95% CI: 0.31–0.98). This effect was similar for post-menopausal breast cancer cases. In addition, the high (vs. low) MeDiet score was associated with 55% decreased risk of hormone receptor positive breast cancer (HR:0.45, 95% CI:0.23–0.87). Neither of the scores calculated on the basis of dietary intakes in the study population (i.e., aMED, MDS) was associated with breast cancer risk. Conclusions: In this large prospective cohort, scores based on recommended intakes of relevant Mediterranean diet foods may lead to strong evidence of the inverse relation between a Mediterranean dietary pattern and incidence of breast cancer among women aged 30 years old or older in the US. Funding Sources: The Framingham Heart Study.